Design and Construction of a Web-Based Outpatient Data Management Information System (Case Study: UPTD Puskesmas Cikampek) - Ardiansyah, Dian; Hayati, Nung; Walim; Yuliandari, Dewi; Supriatin; Lase, Mareanus (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The focus of this research is the design and development of an information system to manage outpatient data at the UPTD Cikampek Health Center which operates via the internet. The purpose of this system is to overcome the problem of inefficient manual recording at the cashier and to improve efficiency and accuracy in managing patient data. A prototype model is used in software development. This model includes steps such as needs analysis, system design, implementation, and testing. The results of this study are in the form of a web-based information system that includes login features, patient data management, payments, reports, and transaction history. It is expected that this system can help exchange information online throughout the scope of the Health Center, accelerate the distribution of reports, and facilitate the management of patient data. Therefore, this study offers an innovative and practical solution to managing health data at first-level health care facilities.